Human myiasis survey in Ilam Province, Southwest of Iran - Morteza Akbari; Javad Rafinejad; AHMAD-ALI HANAFI-BOJD; Ali Ashraf Aivazi; Akbar Biglarian; SORAYA SHEIKHI; ZAHRA SHAVALI; KAMRAN AKBARZADEH (Smujo International, 2020)
Abstract. Akbari M, Rafinejad J, Hanafi-Bojd AA, Aivazi AA, Biglarian A, Sheikhi S, Shavali Z, Akbarzadeh K. 2020. Human myiasis survey in Ilam Province, Southwest of Iran. Nusantara Bioscience 12: 143-147. Myiasis is the infestation of live human and vertebrate animals with dipterous larvae, which at least for a period. Ilam Province of Iran is one of the most important animal husbandry areas, especially nomadic, in Iran. The objective of this study was to identify the prevalence of myiasis in shepherds in Ilam Province. A cross-sectional study was conducted among the shepherds in Ilam Province, western Iran. Out of the 11 counties in Ilam Province, 6 were randomly chosen from three different climates for this study. A questionnaire was used by a trained interviewer to obtain the information from subjects. The disease has been seen in spring, summer, and autumn seasons. About 94.1% of people have been infested at least once. Pharyngeal myiasis had the highest prevalence with 58.3%. Itchy, painful throat, sneeze, cough, and headache were common symptoms. About 85.1% of people described the symptoms of the disease as severe and very severe. About 75.4% stated that the duration of the disease was more than 5 days. According to the results of the study, it was found that the prevalence of myiasis among shepherds in the Ilam Province is high and it is necessary to take appropriate measures to control the disease and increase health literacy.